Is Alpha-Synuclein Loss-of-Function a Contributor to Parkinsonian Pathology? Evidence from Non-human Primates - Collier, Timothy J.; Redmond, D. Eugene; Steece-Collier, Kathy; Lipton, Jack W.; Manfredsson, Fredric P. (Frontiers in Neuroscience, 2016)
Accumulation of alpha-synuclein (α-syn) in Lewy bodies and neurites of midbrain dopamine neurons is diagnostic for Parkinson’s disease (PD), leading to the proposal that PD is a toxic gain-of-function synucleinopathy. Here we discuss the alternative viewpoint that α-syn displacement from synapses by misfolding and aggregation results in a toxic loss-of-function. In support of this hypothesis we provide evidence from our pilot study demonstrating that knockdown of endogenous α-syn in dopamine neurons of nonhuman primates reproduces the pattern of nigrostriatal degeneration characteristic of PD.